Advances in Plasma Treatment of Textile Surfaces - Ul Islam, Shahid; Ul Islam, Shahid; Haji, Aminoddin (Woodhead Publishing, 2024)
Advances in Plasma Treatment of Textile Surfaces offers a detailed overview on the use of plasma in natural and synthetic textiles, and also explores recent applications in technical textiles including composites, ballistic performance, functionalization and textile wastewater treatment.This promising technology can alter the surface properties of textiles without having a significant effect on their bulk properties, leading to potential improvements to the scouring, de-sizing, dyeing, finishing, printing, and laminating processes among others.Drawing on an international team of contributors from industry as well as academia, this important book is bringing these innovative sustainable plasma treatments to textile and polymer scientists everywhere working in the field of textile functionalization. - Provides detailed technical descriptions of cutting-edge applications of plasma in nanotechnology, biotechnology, and other fields - Describes the different kinds of plasma treatment equipment and compares their use for different effects - Starts with overviews of basic information such as how to determine surface properties